2017
DOI: 10.1111/cen.13294
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant alterations of metabolic parameters, cardiovascular risk factors and altered cortisol secretion in patients with adrenal incidentalomas during prolonged follow‐up

Abstract: New-onset ACS developed in 31% patients with NFAI, whereas 21% of NFAI patients had H-UFC levels. All AI patients as a group and the subgroups of N-UFC, H-UFC, C-ACS and ACS patients developed deterioration of metabolic parameters during follow-up that was more prominent in ACS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 39 publications
6
27
0
Order By: Relevance
“…Despite the growing number of studies evidencing a higher frequency of these isolated components of metabolic syndrome in the NFAI population, [18][19][20][21][22][23] it has been assumed this is the first clinical study to evaluate and classify patients with NFAI by different Some studies have also demonstrated higher frequencies of metabolic syndrome components in NFAI patients. [18][19][20][21][22][23] In this context, our results are in line with previous reports, which have demonstrated increased frequency of glucose and lipid disturbances and arterial hypertension. In a multicenter urban Brazilian population study, the prediabetes rate in the 60-to 69-year-old group was 11.2%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the growing number of studies evidencing a higher frequency of these isolated components of metabolic syndrome in the NFAI population, [18][19][20][21][22][23] it has been assumed this is the first clinical study to evaluate and classify patients with NFAI by different Some studies have also demonstrated higher frequencies of metabolic syndrome components in NFAI patients. [18][19][20][21][22][23] In this context, our results are in line with previous reports, which have demonstrated increased frequency of glucose and lipid disturbances and arterial hypertension. In a multicenter urban Brazilian population study, the prediabetes rate in the 60-to 69-year-old group was 11.2%.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, patients with NFAI presented a higher frequency of all criteria for metabolic syndrome (hypertension, hyperglycaemia, dyslipidaemia, increased waist circumference) and a greater metabolic syndrome frequency by four different classifications compared to controls. Despite the growing number of studies evidencing a higher frequency of these isolated components of metabolic syndrome in the NFAI population, it has been assumed this is the first clinical study to evaluate and classify patients with NFAI by different metabolic syndrome criteria defined by globally recognized institutions, and to compare them to controls with normal adrenal imaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zelinka et al showed that pheochromocytoma was associated with endothelial dysfunctions and, established further atherosclerosis (23). However; previous studies reported that nonfunctional adrenal adenoma was associated with an increased cardio-metabolic disturbance (30) including hypertension (31), insulin resistance or diabetes (12,17). Nonfunctional adrenal adenomas have shown to be associated with increased risk of cardiovascular events (17), and mortality (14).…”
Section: Discussionmentioning
confidence: 99%